Delay to treatment for Latinos diagnosed with lung and head-and-neck cancers: application of the behavioral model for vulnerable populations - Scott, Katie L., author; Bloom, Larry, advisor; Borrayo, Evelinn, committee member; Brown, Mark, committee member; Davalos, Deana, committee member (Colorado State University. Libraries, 2013)
Since the enactment of the National Cancer Act of 1971, many Americans have seen improved rates of survival from cancer. However, this is not true of all ethnic groups, and Latino cancer patients in particular tend to have poorer survival rates than those from other ethnic groups. The timely and appropriate treatment of lung and head-and-neck cancers is an especially serious matter because of the relative complexity of these cancers as well as the high mortality risks associated with them. This study applied a well-known theoretical model of health care access and utilization, the Behavioral Model for Vulnerable Populations, to examine factors related to time from diagnosis to first treatment for Latino patients diagnosed with lung and head-and-neck cancers. Using a mixed method design, medical chart reviews were conducted on 53 Latinos diagnosed with lung or head-and-neck cancer, and interviews and focus groups were conducted with five Latino head-and-neck and four lung cancer patients, six caregivers, seven key informants, and seven patient navigators. A model including predisposing (age, gender, country of origin, and language), enabling (insurance status and regular dwelling), and need factors (site of cancer, stage of cancer at diagnosis and number of co-occurring illnesses) accounted for 32% of the variance in time from diagnosis to first treatment. Number of co-occurring illnesses was the only significant predictive factor, demonstrating that with each additional comorbid condition, delay from diagnosis to treatment decreased by 18.72 days. An interaction between number of comorbid conditions and gender revealed that females with a low number of cooccurring illnesses tend to experience the longest delays from diagnosis until treatment. The qualitative data provided support for the influence of predisposing, enabling, and need factors as well as suggested several additional factors that were not analyzed through the medical chart reviews. These additional factors may account for a portion of the remaining variance in time from diagnosis to treatment. This study underscores the need for continued efforts to examine and consider these factors and to utilize them to work to ameliorate delays in time to treatment.
Keywords: cancer; cancer treatment; head-and-neck cancer; Latino population; lung cancer; vulnerable population